Evaluating the Impact of Financial Management Practices on an Organization’s Financial Performance: A Case Study of Hwange Colliery Company - Wadesango, Newman; Ruwende, Justice Walter; Sitsha, Lovemore (International Journal of Economics and Financial Issues, 2023)
The purpose of the study was to establish the impact of financial management practices on an organization’s financial performance. This analysis was driven by the organization’s declining profitability despite the efforts to deploy cost-cutting initiatives. As a consequence, the research looked into the impact of existing procedures in working capital management, fixed assets management, capital structure and investment practices. The descriptive research design was used in the study and quantitative research approach was adopted. The administrative personnel at Hwange Colliery Company, which numbered forty six, comprised the population and a sample of 30 was used. A questionnaire survey with structured questions was utilized. In the study, regression analysis and Pearson coefficient of correlation were employed to determine the link between the factors of financial performance and financial management techniques. It emerged that the financial management strategies had a substantial impact on Hwange Colliery Company financial performance. To maintain resource efficiency, the research recommends improvements in the areas of accounts receivable management and investment decision that is leading to losses if wrong decision are made.